2014
DOI: 10.3390/bios4030221
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Magnetic Directions in Birds: Radical Pair Processes Involving Cryptochrome

Abstract: Birds can use the geomagnetic field for compass orientation. Behavioral experiments, mostly with migrating passerines, revealed three characteristics of the avian magnetic compass: (1) it works spontaneously only in a narrow functional window around the intensity of the ambient magnetic field, but can adapt to other intensities, (2) it is an “inclination compass”, not based on the polarity of the magnetic field, but the axial course of the field lines, and (3) it requires short-wavelength light from UV to 565 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 94 publications
3
69
0
Order By: Relevance
“…The same is true for a RPM, which appears likely to play at least some role in the turtles SMA (Landler et al, 2015). The putative receptive molecule for a RPM is cryptochrome (Wiltschko and Wiltschko, 2014;Niebner et al, 2011;Liedvogel and Mouritsen, 2010;Gegear et al, 2008), a molecule best known for its role in circadian rhythms (Ye et al, 2014). The involvement of cryptochrome in the magnetic compass is consistent with most behavioral and histological evidence (Wiltschko and Wiltschko, 2014).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The same is true for a RPM, which appears likely to play at least some role in the turtles SMA (Landler et al, 2015). The putative receptive molecule for a RPM is cryptochrome (Wiltschko and Wiltschko, 2014;Niebner et al, 2011;Liedvogel and Mouritsen, 2010;Gegear et al, 2008), a molecule best known for its role in circadian rhythms (Ye et al, 2014). The involvement of cryptochrome in the magnetic compass is consistent with most behavioral and histological evidence (Wiltschko and Wiltschko, 2014).…”
Section: Discussionmentioning
confidence: 65%
“…The putative receptive molecule for a RPM is cryptochrome (Wiltschko and Wiltschko, 2014;Niebner et al, 2011;Liedvogel and Mouritsen, 2010;Gegear et al, 2008), a molecule best known for its role in circadian rhythms (Ye et al, 2014). The involvement of cryptochrome in the magnetic compass is consistent with most behavioral and histological evidence (Wiltschko and Wiltschko, 2014). Recently, it has been shown that a zinc ion serves as a cofactor in cryptochrome photochemical reactions (Schmalen et al, 2014).…”
Section: Discussionmentioning
confidence: 91%
“…Interpretable magnetic information mediated by the left eye is essentially required to remove the lateralization. When the left eye system is activated, it can adjust to intensities outside the functional window of the magnetic compass (see [32]), but if it does, this ability is not transferred to the right eye system. The directional information from the magnetic field originates in the retina and is transmitted by the visual nerve to higher centers in the brain (e.g., [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Interpretable magnetic information mediated by the left eye is essentially required to remove the lateralization. When the left eye system is activated, it can adjust to intensities outside the functional window of the magnetic compass (see [32]), but if it does, this ability is not transferred to the right eye system.…”
Section: Discussionmentioning
confidence: 99%
“…And, because the photoreceptors are aligned in perfect hemispheres, retinae are ideal antennas. In an experiment with birds and yellow filter glasses upon their eyes, the birds had no blue light radicals anymore, and -consequently no directional information means the birds lost orientation [62].…”
Section: Equivalent Counterpart In the Organism?mentioning
confidence: 99%